Gastroesophageal Reflux Disease-Related Asthma: Neurogenic Inflammation and Non-pharmacological Management - Wibowo, Adityo (Medula, 2025)
Asthma is a chronic inflammatory disease of the airways, characterized by bronchoconstriction, airway remodeling, and increased responsiveness to non-specific stimuli. While childhood-onset asthma is commonly associated with allergens, adult-onset asthma is linked to environmental and individual factors. One significant contributor to adult-onset asthma is gastroesophageal reflux disease (GERD), which exacerbates asthma symptoms through microaspiration and vagally mediated reflexes. GERD is a chronic gastrointestinal disorder characterized by acid reflux into the esophagus, influenced by factors such as obesity, tobacco use, and stress. Studies indicate a strong association between GERD and asthma, with approximately 80% of asthmatic individuals experiencing heartburn or regurgitation. GERD-induced neurogenic inflammation contributes to airway hyperreactivity and bronchospasm. Non-pharmacological interventions, including dietary modifications, weight loss, smoking cessation, and elevating the head during sleep, have shown efficacy in reducing reflux symptoms and improving asthma control.